Is intravesical prostatic protrusion a risk factor for hydronephrosis and renal insufficiency in benign prostate hyperplasia patients?. Issue 5 (May 2019) - Lu, Chin-Heng; Wu, Howard H.H.; Lin, Tzu-Ping; Huang, Yi-Hsiu; Chung, Hsiao-Jen; Kuo, Junne-Yih; Huang, William J.; Lu, Shing-Hwa; Chang, Yen-Hwa; Lin, Alex T.L.
Abstract : Background: Some patients with benign prostatic hyperplasia (BPH) and lower urinary tract symptoms hesitate to undergo surgical treatment until acute urinary retention (AUR) occurs. Some of these patients have been found to have hydronephrosis or even renal insufficiency. This study aimed to analyze the risk factors for hydronephrosis in patients with AUR who needed to receive transurethral resection of the prostate (TURP). Methods: We retrospectively analyzed 91 patients from January 2014 to June 2015, who had BPH and received TURP for AUR. Patients with urolithiasis, prostate cancer, bladder cancer, gross hematuria, previous bladder radiation therapy, or urinary tract surgery were excluded. Parameters of intravesical prostatic protrusion (IPP), serum prostatic specific antigen (PSA), total prostate volume (PV), age, body mass index (BMI), hypertension (HTN), diabetes mellitus (DM), coronary artery disease (CAD), and serum creatinine (Cr) were compared between the hydronephrosis and non-hydronephrosis groups. Results: There were significant differences in IPP ( p < 0.001) and Serum Cr ( p < 0.001) between the hydronephrosis and non-hydronephrosis groups. For IPP, the cut-off values of the highest risk of hydronephrosis was 1.95 cm. There were no significant differences in age, BMI, DM, HTN, CAD, total PV, and PSA between the two groups. IPP was not correlated with total PV ( p = 0.423). Most of the patients with hydronephrosis had renal function improvement after TURP. Conclusion: IPP was a significant risk factor for hydronephrosis in BPH patients. If the patients' IPP exceeded 1.95 cm, they had a higher risk of having hydronephrosis when AUR occurred. Hydronephrosis is a risk factor for renal insufficiency, and Serum Cr levels decreased significantly in the patients of our study.